School Violence in the Emirate of Sharjah - Al-Teneijii, Noura Mohammed; Alomosh, Ahmad Falah (Al-Adab Journal, 2021)
The study aims to investigate school violence in the Emirate of Sharjah. It explores the forms, manifestations, causes and solutions of school violence to reduce them. A special questionnaire was designed for the study, and it was applied to the students of the Emirate of Sharjah by using the non-probability purposive sampling method. The total number of the study subjects is 137 students; (35) male and (102) female students.The study orders the forms of school violence descending according to their degree of severity as follows: violence directed by the teaching staff towards students, violence directed by students towards their fellow students, violence directed by students towards school properties and finally, violence directed by students towards teachers. The study also revealed the causes of school violence and proposed alleviating solutions.Among the important findings of the study is that excessive parental indulgence, control over the child and deprivation of pocket money are not among the factors that lead to violence. However, the most important things that lead to violence are dealing with bad companions, the absence of school guidance and counseling, the conditions of life during the stage of adolescence and failure to exploit free time with meaningful activities that promote children’s talents.